Characterization of Homeodomain Proteins at the Aβ Sublocus in Schizophyllum commune and Their Role in Sexual Compatibility and Development - Chen Chu; Dongxu Li; Changhong Liu (Journal of Fungi, 2025)
The A mating-type locus in Schizophyllum commune, which encodes homeodomain (HD) transcription factors, is essential for regulating sexual compatibility and development. While the role of the Aα sublocus and its Y-Z HD protein complex is adequality understood, the function of HD proteins at the Aβ sublocus remains unclear. In this study, we analyzed the Aβ sublocus of eight monokaryotic S. commune strains derived from the parental dikaryotic strain 20R-7-Z01 and identified four HD genes, abr, abs, abv, and abq, located at the Aβ sublocus. These genes encode two HD1 proteins (S and Q) and two HD2 proteins (R and V). Protein structure prediction, interaction assays, and in vivo functional analyses revealed that R-S and V-Q interactions independently regulate sexual compatibility and fruiting body development. This research highlights the critical role of the Aβ sublocus in fungal reproduction and provides valuable insights for breeding edible and medicinal S. commune strains.